Draft Genome Sequence of a Mycobacterium heckeshornense Clinical Isolate - Ustinova, V. (Genome Announc, 2018)
We report here the draft genome sequence of Mycobacterium heckeshornense, isolated from the sputum of a patient admitted to a tuberculosis hospital with suspected pulmonary tuberculosis.